Drosophila melanogaster: A Model Organism to Study Cancer - Mirzoyan, Zhasmine; Sollazzo, Manuela; Allocca, Mariateresa; Valenza, Alice Maria; Grifoni, Daniela; Bellosta, Paola (Frontiers in Genetics, 2019)
Cancer is a multistep disease driven by the activation of specific oncogenic pathways concomitantly with the loss of function of tumor suppressor genes that act as sentinels to control physiological growth. The conservation of most of these signaling pathways in Drosophila, and the ability to easily manipulate them genetically, has made the fruit fly a useful model organism to study cancer biology. In this review we outline the basic mechanisms and signaling pathways conserved between humans and flies responsible of inducing uncontrolled growth and cancer development. Second, we describe classic and novel Drosophila models used to study different cancers, with the objective to discuss their strengths and limitations on their use to identify signals driving growth cell autonomously and within organs, drug discovery and for therapeutic approaches.